Changing Pattern of Congenital Heart Disease Care During COVID-19 Pandemic - Sachdeva, Sakshi (Indian J Pediatr, 2021)
OBJECTIVE: To study the impact of coronavirus disease 2019 (COVID-19) pandemic on the utilization of pediatric cardiac care services and to determine the role of teleconsultation services in delivering healthcare in this subset of population. METHODS: It was a retrospective, observational study. All children who attended pediatric cardiology outpatient/teleconsultation services or were admitted to pediatric cardiology ward between April 1, 2019 to July 31, 2019 and April 1, 2020 to July 31, 2020, were recruited in the study. Data for patients who underwent surgery or catheter intervention for congenital heart disease were also recorded and analyzed. Comparisons were drawn between the statistics during the two time-periods. RESULTS: Physical outpatient services were discontinued and were replaced by teleconsultations from April 2020. Inpatient admissions during COVID-19 pandemic (n = 66) decreased by two-thirds as compared to the admissions during similar period in 2019 (n = 189). Similarly, the percentage decrease during these 4 mo of pandemic were 84% for catheter interventions, 88% for total congenital heart disease (CHD) surgeries, and 40% for emergency CHD surgeries. The number of patients availing successful teleconsultation was 1079, which was only 15% of the total number of patients attending physical outpatient services (n = 7176) during the corresponding period in the year 2019. During the pandemic, systematic teleconsultation and local evaluation and investigations aided in better management of patients with CHD. CONCLUSIONS: The utilization of cardiovascular services for CHD has reduced significantly during COVID-19 pandemic, for both out- and inpatient care. Teleconsultation services have streamlined the follow-up care to some extent and have helped in noncontact triaging of these patients for further care.